Sistem Monitoring dan Kontrol Taman Pintar Berbasis IoT (Internet of Things) dengan NodeMCU ESP8266 - Syahrul Gunawan; Abdul Halim Anshor; Amali Amali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Parks are recreational areas that are often visited by people to relax and unwind. However, sometimes parks are not well-maintained and become less attractive to visitors. The lack of park maintenance is often due to a shortage of human resources and inefficiencies in monitoring park conditions. Therefore, this research aims to address this issue by developing a Internet of things-based Smart Park monitoring and control system using NodeMCU ESP8266. This system allows park managers to monitor and control park conditions in realtime from a distance using parameters such as soil moisture, air humidity, temperature, and watering. This research uses a prototype method with stages of requirement analysis, system design, implementation, and evaluation. The Smart Park system was successfully implemented using NodeMCU ESP8266 and integrated with a telegram bot as a means of remote monitoring and control. This telegram bot allows park managers to check park environmental parameters. The integration of the Smart Park system with telegram bot has been proven effective in increasing park maintenance efficiency. The results of the study show that park managers can monitor park conditions more easily, thus reducing the burden on park managers.